2017
DOI: 10.1038/cmi.2016.72
|View full text |Cite
|
Sign up to set email alerts
|

Loss of T-cell protein tyrosine phosphatase in the intestinal epithelium promotes local inflammation by increasing colonic stem cell proliferation

Abstract: T-cell protein tyrosine phosphatase (TC-PTP) has a critical role in the development of the immune system and has been identified as a negative regulator of inflammation. Single-nucleotide polymorphisms in the TC-PTP locus have been associated with increased susceptibility to inflammatory bowel diseases (IBDs) in patients. To further understand how TC-PTP is related to IBDs, we investigated the role of TC-PTP in maintaining the intestinal epithelial barrier using an in vivo genetic approach. Intestinal epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Ptpn2 +/-BALB/c mice have been previously described (12). Generation of Ptpn2-floxed (Ptpn2 fl/fl ) B6 mice has recently been described (49). B6 mice congenic for the…”
Section: Methodsmentioning
confidence: 99%
“…Ptpn2 +/-BALB/c mice have been previously described (12). Generation of Ptpn2-floxed (Ptpn2 fl/fl ) B6 mice has recently been described (49). B6 mice congenic for the…”
Section: Methodsmentioning
confidence: 99%
“…The dephosphorylation of pSTAT1 in TC-PTP deficient mouse fibroblasts was strongly delayed, resulting in the expression of STAT1 target genes. Bussieres-Marmen et al demonstrated that the knockout of TC-PTP in the intestinal epithelial cells in mice resulted in severe colitis corresponding with increased inflammation and increased cell proliferation via the activation of STAT1 [ 145 ]. Interestingly, genetic variations in PTPN2 have been associated with the chronic inflammatory bowel disease known as Crohn’s disease [ 146 ].…”
Section: T-cell Protein Tyrosine Phosphatasementioning
confidence: 99%
“…62 In regard to cancer, intestinal epithelial cell-specific deletion of TC-PTP led to an increase in colonic stem cell proliferation, resulting in elevated susceptibility to injuries, such as dextran sulfate sodium (DSS)induced colitis, implying TC-PTP could serve as a tumor suppressor in colon cancer. 63 Global TC-PTP-deficient mice revealed that loss of TC-PTP in mammary fat pads resulted in a significant increase in both SFK and STAT3 signaling pathways, suggesting a tumor suppressive role for TC-PTP in breast cancer. 55 Collectively, the current research findings from in vivo studies have revealed that not only is TC-PTP a crucial modulator in immune functions, but it also may play an important role in the development of the disease, including cancer.…”
Section: Specific Deletion Of Tc-ptp In T Cells Resulted In the Develmentioning
confidence: 99%
“…Pancreatic–specific TC‐PTP deletion in mice demonstrated that TC‐PTP could contribute to the progression of cerulean‐induced acute pancreatitis by increasing the levels of inflammatory cytokines TNF‐α and IL‐6 and NF‐kB‐mediated inflammation . In regard to cancer, intestinal epithelial cell‐specific deletion of TC‐PTP led to an increase in colonic stem cell proliferation, resulting in elevated susceptibility to injuries, such as dextran sulfate sodium (DSS)‐induced colitis, implying TC‐PTP could serve as a tumor suppressor in colon cancer . Global TC‐PTP‐deficient mice revealed that loss of TC‐PTP in mammary fat pads resulted in a significant increase in both SFK and STAT3 signaling pathways, suggesting a tumor suppressive role for TC‐PTP in breast cancer .…”
Section: Tc‐ptp Function: Lessons From Mouse Models Of Tc‐ptpmentioning
confidence: 99%